Australian Professional Library and Information Studies Education Programs:Changing Structure and Content. Issue 4 (1st October 2016) - Willard, Patricia; S Wilson, Concepcion
ABSTRACT: Australian library and information studies professional education experienced major changes over the past 15 years or so. There has been a growth in first professional level masters programs. Some schools have been involved in organisational relocation. Program structural changes have aimed to make programs more flexible and appealing to prospective students. These changes have not produced increased enrolmellls; rather, enrolments have fallen.